2006
DOI: 10.1128/jb.188.6.2275-2279.2006
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Analysis of Iron-Inducible Genes in Magnetospirillum magneticum AMB-1

Abstract: Iron uptake systems were identified by global expression profiling of Magnetospirillum magneticum AMB-1. feo, tpd, and ftr, which encode ferrous iron transporters, were up-regulated under iron-rich conditions. The concomitant rapid iron uptake and magnetite formation suggest that these uptake systems serve as iron supply lines for magnetosome synthesis.Iron is crucial in microbial metabolism. It exists in two redox states: the reduced Fe 2ϩ soluble ferrous state and the oxidized Fe 3ϩ ferric form, which is ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 27 publications
(26 reference statements)
3
58
0
Order By: Relevance
“…Of the total iron taken up by the cells, 75% is consumed in the first 15 min and 86% in the first 30 min. This result is supported by recent iron-uptake gene studies that also show significant cellular iron uptake within 10 min of induction, which is similar to the results presented here (19). The magnetic optical density (C mag ) is a qualitative measure of the cells' magnetization (20).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Of the total iron taken up by the cells, 75% is consumed in the first 15 min and 86% in the first 30 min. This result is supported by recent iron-uptake gene studies that also show significant cellular iron uptake within 10 min of induction, which is similar to the results presented here (19). The magnetic optical density (C mag ) is a qualitative measure of the cells' magnetization (20).…”
Section: Resultssupporting
confidence: 78%
“…Rapid magnetosome formation appears correlated with respiratory growth under microaerobic conditions at low pO2; the slower magnetosome formation reported by Komeili was for bacteria grown anaerobically with nitrate as the terminal electron acceptor, and hence energy production would be lower. However, the secondary phase of maturation from small, immature magnetite crystals of 5-20 nm into perfect cubooctahedral particles, previously observed for both M. gryphiswaldense MSR-1 and M. magneticum AMB1 (17,19), appears much shorter in our studies.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…To identify global gene expression profiles, especially those of iron uptake genes under different iron concentrations, transcriptome analysis through microarray imprinted with DNA from the whole genome sequence of AMB-1 was investigated (Suzuki et al 2006). Three ferrous and two ferric iron uptake systems encoded by specified genes were identified from the genome sequence, and two distinct patterns were observed in relation to the iron concentration in the growth medium and gene expression.…”
Section: Gene Expression Analysis Of Iron-inducible Genesmentioning
confidence: 99%
“…The various crystal morphologies and compositions observed are species or strain dependent, implying a high degree of biological control (Spring and Schleifer 1995). Recent comprehensive molecular studies, including proteomic (Okamura et al 2000;Grünberg et al 2001Grünberg et al , 2004Arakaki et al 2003;Tanaka et al 2006), transcriptomic Suzuki et al 2006;Würdemann et al 2006), and whole-genomic analyses (Matsunaga et al 2005;Schübbe et al 2009), have revealed that the proteins associated with these particles play key roles in magnetosome biomineralization (Nakamura et al 1995;Arakaki et al 2003;Komeili et al 2006;Scheffel et al 2006). On the basis of the results of these studies, it has been described that the mechanism underlying magnetosome formation involves multiple processes including vesicle formation and alignment (Komeili et al 2006;Scheffel et al 2006), vesicular iron accumulation (Nakamura et al 1995), and iron-oxide crystallization (Arakaki et al 2003).…”
mentioning
confidence: 99%